ChemInform Abstract: Cobalt‐Catalyzed Hydroarylative Cyclization of 1, 6‐Enynes with Aromatic Ketones and Esters via C—H Activation. Issue 7 (29th January 2015) - Santhoshkumar, Rajagopal; Mannathan, Subramaniyan; Cheng, Chien‐Hong
Abstract The highly chemo‐ and stereoselective title reaction furnishes functionalized pyrrolidines and dihydrofurans via cobalt‐triggered C‐H activation.